2019
DOI: 10.3844/ajidsp.2019.115.122
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistant Uropathogens among Egyptian Pregnant Women

Abstract: Urinary Tract Infections (UTIs) in pregnancy is a common medical problem associated with significant increase in the risk of fetal morbidity and mortality. The effective appropriate antimicrobial agent is a major concern as many effective antimicrobial groups cannot be used due to their potential toxicity to the fetus as well as the increasing rates of Multidrug-Resistant (MDR) strain isolation. This crosssectional study was conducted on women attending the antenatal care of Zagazig University. This study aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
4
7
0
Order By: Relevance
“…pneumoniae (37.9%) was the most common CR species isolated followed by E. coli (24.1%). This is in agreement with other CR studies in Egypt, United States, Europe and China (Metwally and Elnagar, 2019;Centers for Disease Control and Prevention, 2013;Akova et al, 2012;Yang et al, 2018) and is consistent with the CDC's recommendations that K. pneumoniae, E. coli, and Enterobacter spp. are the key health care-associated pathogens to focus on in the control of US CR epidemic (Centers for Disease Control and Prevention, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…pneumoniae (37.9%) was the most common CR species isolated followed by E. coli (24.1%). This is in agreement with other CR studies in Egypt, United States, Europe and China (Metwally and Elnagar, 2019;Centers for Disease Control and Prevention, 2013;Akova et al, 2012;Yang et al, 2018) and is consistent with the CDC's recommendations that K. pneumoniae, E. coli, and Enterobacter spp. are the key health care-associated pathogens to focus on in the control of US CR epidemic (Centers for Disease Control and Prevention, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Among the tested antimicrobial agents, carbapenems and aminoglycoside were the most effective options, this finding is similar to those of Chaudhary et al [16]. Pervious study had indicated that Gram negative uropathogens exhibited excellent sensitivity to meropenem and aztreonam [24]. This study showed that 65.8% of Gram-negative bacteria were confirmed to be ESBL producer by combined disc test, this comes in accordance with some studies [14,25], lower rates were reported in other studies [24,26].…”
Section: Discussionsupporting
confidence: 89%
“…Lower rates were reported in some studies [16,31]. Other Egyptian studies showed variable isolation rates of MDR ranging from 37.2 to 95%, with observed chronologically increasing rates [14,24,32].…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, UTI was more frequent (70%) among full-term neonates (Mohamed et al 2020). Escherichia coli is the most common etiologic agent and the most widespread cause (75-95%) of UTI worldwide (Lee and Le 2018;Metwally and Elnagar 2019;Prasada et al 2019;Bazzaz et al 2021). Several studies from Egypt revealed that the most frequent microorganisms causing UTI were E. coli (30Á7-74%), followed by Staphylococcus aureus (17Á5À21Á1%) and Klebsiella spp.…”
Section: Introductionmentioning
confidence: 99%